2009
DOI: 10.1063/1.3273206
|View full text |Cite
|
Sign up to set email alerts
|

Solvation and microscopic properties of ionic liquid/acetonitrile mixtures probed by high-pressure infrared spectroscopy

Abstract: The microscopic features of binary mixtures formed by an ionic liquid (EMI(+)TFSA(-) or EMI(+)FSA(-)) and a molecular liquid (acetonitrile or methanol) have been investigated by high-pressure infrared spectroscopy. On the basis of its responses to changes in pressure and concentration, the imidazolium C-H appears to exist at least in two different forms, i.e., isolated and associated structures. The weak band at approximately 3102 cm(-1) should be assigned to the isolated structure. CD(3)CN can be added to cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
28
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 50 publications
0
28
0
Order By: Relevance
“…[51][52][53][54] Nevertheless,t here should be ar elationship between the observed and calculated frequencies. [56][57][58] In contrast to the present work, the interactions between the ionic liquid anda cetonitrilew ere not mentioned in the reportb yU mebayashi et al, [47] who even used the term "isolated structure" to describe the ionic liquid in dilute acetonitrile. Figure 2B,t he negative peak corresponds to the species in neat acetonitrile.…”
Section: Resultsmentioning
confidence: 79%
See 1 more Smart Citation
“…[51][52][53][54] Nevertheless,t here should be ar elationship between the observed and calculated frequencies. [56][57][58] In contrast to the present work, the interactions between the ionic liquid anda cetonitrilew ere not mentioned in the reportb yU mebayashi et al, [47] who even used the term "isolated structure" to describe the ionic liquid in dilute acetonitrile. Figure 2B,t he negative peak corresponds to the species in neat acetonitrile.…”
Section: Resultsmentioning
confidence: 79%
“…[47] They observed an increasei nt he imidazolium CÀHi ntensity at approximately 3102 cm À1 upon mixing acetonitrile with the ionic liquid. [47] They observed an increasei nt he imidazolium CÀHi ntensity at approximately 3102 cm À1 upon mixing acetonitrile with the ionic liquid.…”
Section: Resultsmentioning
confidence: 98%
“…It is well known that high pressures almost invariably cause phase changes and the pure ionic liquids will most likely be frozen, i.e., in solid form. [27][28][29] The sharper structures revealed in Fig. 2(b) is in part due to the conformation drift and anisotropic environment in a solid structure.…”
Section: Methodsmentioning
confidence: 99%
“…The pressures used to investigate chemical systems typically range from ambient to several GPa; such pressures mainly change intermolecular distances and affect conformations. [27][28][29][30] Previous high-pressure measurements indicated that acetonitrile and dimethyl sulfoxide can be added to change the structural organization of ionic liquids. 27,28 Under ambient pressure, Raman spectra indicate that the more thermodynamically stable butyl structure of the cations is the gauche-anti (GA) and all-anti forms for [BMI][Br] and [BMI][Cl], respectively.…”
Section: Introductionmentioning
confidence: 99%
“…Generally, RTILs are classified into several groups depending on the cationic series, imidazolium, pyridinium, and alphatic quaternary ammonium series. Most of studies so far concern with the results at atmospheric pressure, but recently an increasing number of works using high pressure is reported (Chang et al, 2007(Chang et al, , 2008a(Chang et al, , 2008b(Chang et al, , 2008cSu et al, 2009Su et al, , 2010Umebayashi et al, 2009aUmebayashi et al, , 2009b. A merit of the use of high pressure as a varialbe is summarized as follows.…”
Section: Introductionmentioning
confidence: 99%